Condicionantes da distribuição de renda e da pobreza no Brasil nas décadas de 1960 a 2000 - Lernic, Carolina de Almeida (2015)
This study aimed to conduct a study on the main variables that influence poverty and income concentration, and through these data, compared the main policies implemented, between the decades from 1960 to 2010, which eased or worsened these issues in Brazil. Were taken as basic social indicators as Gini Index, Poverty Line, Wages, Employment index. Viewing a successive overview of three decades - 1960, 1970 and 1980 - it is concluded that there were times in which an improvement in income distribution and poverty was real, in 1970, for example, however, due to the fragility of the Brazilian economy, this situation could not be sustained for long. In an overview, the Real Plan promoted the resumption of economic growth, through the control of inflation. However, it is mainly in the 2000s, that displaying major improvements in the levels of concentration of wealth and poverty